DEVELOPMENT AND EVALUATION OF GERMINATED BROWN RICE IN CORPORATED NANKHATAI - V. HEMALATHA, B. MOUNIKA, S. SUCHIRITHA DEVI, K. UMA MAHESWARI and (The Journal of Research, PJTSAU, 2019)
The demand for processed and convenience food is increasing constantly due to urbanization, changing lifestyle and food habits of the people (Sheereen, 2013). Development of fortified biscuits or other composite flour bakery products is the latest trend in bakery industry. The growing interest in these types of bakery products is due to their better nutritional properties and possibility of their use in feeding programs and in situations like starvation or earthquakes (Pratima and Yadava, 2000).